Yurisdiksi Kelompok Pemberontak Pra dan Pasca Pengakuan Sebagai Subjek Hukum Internasional - Chusnein, Akbar; Putra, Akbar Kurnia (Faculty of Law, Universitas Jambi, 2021)
This research aims to provide a general understanding of the jurisdiction for rebel groups before and after their recognition as belligerents, or the shift of the groups in question from domestic legal subjects to legal subjects of the international law. The type of method used in this research is in the form of normative legal research, which utilizes the collection of legal materials relevant to the object of research in the form of literature; The materials referred to are such as: (a) Primary legal materials: The Charter of United Nation, The Geneva Convention, The Hague Convention; (b) Secondary legal materials: legal science books, legal science journals, legal research reports, scientific articles, seminar materials, workshops, and so on; (c) Tertiary legal materials: Legal materials which precepts or provides an explanation on the primary and secondary legal materials, such as legal dictionaries, newspapers, the internet and so on.